Work Discipline Factors Affecting Employees Performance Of Marketing Subdivision of Madika Foundation In Surabaya - Fajar Tinovitasari; Rika Yuliastanti; Fianita Malati (IJEBD (International Journal of Entrepreneurship and Business Development), 2017)
Purpose : To generate good employee performance, then employee discipline factors need to be improved and maintained continuity. Design/methodology/approach : Research approach, Quantitative approach is research that focuses on testing the hypothesis. Data used should be measurable and will result in generalizable conclusions. This research was causal because it would examine the influence between variables. Findings The result of CAAR is showed that CAAR abnormal return significantly merely happen in research period III. While, for t-test towards AAR showed that abnormal return happened in period II and III tax amnesty execution Research limitations/implications : The object of this research is company which recorded as a member in LQ45 indexes. Practical implications : The result of CAAR is showed that CAAR abnormal return significantly merely happen in research period III. While, for t-test towards AAR showed that abnormal return happened in period II and III tax amnesty execution, with details in period II abnormal return merely happen in t-1 with negative value and period III abnormal return happen in t-9, t-8, t-4, t-3, t+1 and t+9. Originality/value : In improving work discipline, assertiveness imposed on employees who violate discipline should also be noted.